2008
DOI: 10.1002/chem.200701277
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Study on the CC Coupling of Naphthol Catalyzed by CuII⋅TMEDA: Evidence for the Key Role of Binuclear Clusters

Abstract: The mechanism of oxidative coupling of two naphthol molecules to form binaphthol catalyzed by Cu(OH)ClTMEDA (TMEDA=N,N,N',N'-tetramethylethylenediamine) was approached by means of a gas-phase model system. Concise evidence is provided that the coupling reaction proceeds in clusters with two Cu(II) centers, whereby the intermediacy of free naphthoxy radicals in the coupling step is avoided. In the absence of TMEDA, the cluster is bound via a bridging counterion and the coupling reaction is followed by cluster c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…A similar effect of the ortho-substitution of carboxymethyl was observed in the coupling of naphthol [66], which indicates the participation of ortho-ester in binding to the metal center. For ion 9, we postulate that the coordination of ortho-carboxymethyl to nickel weakens the Ni-PPh 3 bonding, which facilitates the leaving of one PPh 3 ligand.…”
Section: Fragmentation Of [Arnisupporting
confidence: 63%
“…A similar effect of the ortho-substitution of carboxymethyl was observed in the coupling of naphthol [66], which indicates the participation of ortho-ester in binding to the metal center. For ion 9, we postulate that the coordination of ortho-carboxymethyl to nickel weakens the Ni-PPh 3 bonding, which facilitates the leaving of one PPh 3 ligand.…”
Section: Fragmentation Of [Arnisupporting
confidence: 63%
“…A gas-phase study of the reaction mechanism of copper(II)-mediated coupling of methyl ester of 2-hydroxy-3-naphthoic acid (NaphOH) in presence of the chelating ligand N,N,N ,N -tetramethylethylenediamine (TMEDA) [195,196] has shown that rather than mononuclear copper complexes [Cu(NaphO)(TMEDA)] + , which do not exhibit any significant radical reactivity, binuclear clusters can serve as essential reaction intermediates [197,198]. In such complexes each naphthol molecule is bound to one copper atom and the coupling reaction occurs between two of these "controlled" radicals (Scheme 4).…”
Section: Methodsmentioning
confidence: 99%
“…This study shows, for the first time, that Cu II salicylate dimer 1 is a powerful catalyst for the aerobic oxidative coupling of amines with carbon‐, nitrogen‐ and phosphorus‐based nucleophiles. Mechanistically, the binuclear Cu II salicylate is distinct from the widely used simple copper salts such as CuBr and CuCl 2 in the CDC . Only in the presence of an oxidant can it oxidize the amine to the iminium intermediate, and this process is notably accelerated by the chloride ion.…”
Section: Resultsmentioning
confidence: 99%